The shabti - Lorenz, Megaera C. (CamCat Publishing, LLC, 2024)
"It's 1934. Former medium Dashiel Quicke travels the country debunking spiritualism and false mediums while struggling to stay ahead of his ex-business partner and lover who wants him back at any cost. During a demonstration at a college campus, Dashiel meets Hermann Goschalk, an Egyptologist who's convinced that he has a genuine haunted artifact on his hands. Certain there is a rational explanation for whatever is going on with Hermann's relics, Dashiel would rather skip town, but soon finds himself falling for Hermann. He agrees to take a look after all and learns that something is haunting Hermann's office indeed. Faced with a real ghost Dashiel is terrified, but when the haunting takes a dangerous turn, he must use the tools of the shady trade he left behind to communicate with this otherworldly spirit before his past closes in."--Amazon